DISABILITAS DALAM KARYA SENI LUKIS ABSTRAK FIGURATIF - RAFID ADLI, Drs. Erfahmi, M.Sn. (Serupa The Journal of Art Education, 2019)
The creation of this final work aims to visualize disability as a concept of painting. Visualization of works displays the atmosphere of neglected persons with disabilities in terms of social, education, employment, and information systems. The method and process of work used in the creation of works, through several stages: (1) preparation, (2) Elaboration, (3) Synthesis, (4) Realization of the concept, (5) Completion. The results of the discussion are visualization of caring, mutual help, and respect for fellow human beings on this earth without comparing physically or mentally. The work discussed above consists of ten abstract figurative paintings with the title: Aku Kamu Sama, With Friends, Jangan Rampas, Jangan Malu, Masa Bodoh, Better To Die, Ditolak, My Path, My Path#2, Ruang Sempit.Kata Kunci: Disabilitas, karya, seni lukis, figuratif.